Free Maternal Health Care Policy in Kenya; Level of Utilization and Barriers - Brian Barasa Masaba; Rose M Mmusi-Phetoe (Elsevier, 2020)
Objectives: The present study aimed to explore the level of utilization and barriers to the free maternal service (FMS) policy, introduced in 2013 in Kenya. Methods: Literature search was on biomedical databases of the most recent available electronic data published, in English. That is between January 2014 and April 2020. The populations for eligible studies were health care providers, stake holders and mothers who sought maternal care in the specified hospitals. All studies eligible were strictly those conducted in Kenya. Results: The search generated 20,638 articles of which only 27 articles met the inclusion criteria. Qualitative analysis was done. The findings and discussion were presented and organized under thematic domains. Conclusion: The major findings of this review show that free maternal services has increased utilisation of the skilled birth attendant among the women who dwell close to the hospitals and who could not afford for the services initially. However there still exists a challenge to the utilization of FMS among the poor women in remote areas. To further improve the efficiency and utilization of FMS, it is recommended 1) more funding to the program, 2) putting in place adequate material/infrastructure and human resources, 3) improving road network in the remote areas and providing incentives to the rural poor women.